Numerical Study of Effects of Bladder Filling on Prostate Positioning In Radiotherapy - Krywonos, J; Elkut, F; Brunt, J; Malik, Z; Eswar, C; Fenwick, J; Ren, X (2009)
The success of radical prostate radiotherapy depends on delivery of high dose radiotherapy to a defined tissue volume with a high degree of positional accuracy. Modern techniques such as conformal and intensity-modulated radiotherapy (IMRT) can deliver increased radiation dose to the tumour without increased toxicity, but at the expense of requiring smaller delineated treatment margins, which is often difficult to control due to complex organ interactions. In prostate cancer radiotherapy, the position of the prostate is influenced by many factors in particular bladder and rectum filling. It is essential to study the mechanics of these processes and its interaction with adjacent structures to improve the understanding of their influences on the position of the intended irradiated area. In this work, a detailed 3D finite element model has been developed using patient specific MRI images to study the interaction between the bladder, prostate and rectum. Bladder filling was simulated by modelling the physical process to predict deformation fields with volume changes. The movement of the prostate associated with Bladder volume change in the anterior-posterior (AP), superior-inferior (SI) and right-left (RL) directions as well its rotational movement has been predicted. The numerical results were compared to repeated images and showed good agreement with some published clinical data. © 2009 Springer Berlin Heidelberg.